Does audit opinion matter to issuance of sukuk? - Azwar, Azwar; Abdullah, Mohd Farid Ravi; Usman, Abur Hamdi (Journal of Islamic Accounting and Finance Research, 2024)
Purpose - This study aims to analyze the effect of The Audit Board of The Republic of Indonesia's audit opinion on Central Government Financial Statement and economic factors on the Government Sharia Securities (sukuk) issuance of Indonesia.Method - The data collected is secondary data obtained from the Audit Board of the Republic of Indonesia (BPK), Bank Indonesia, and World Bank. This study uses a quantitative approach with the Ordinary Least Squares (OLS) technique.Result - The results show that the audit opinion by BPK has a positive and significant influence on the development of sukuk in Indonesia. The inflation rate is found to have a negative effect on sukuk, but not significant. The exchange rate is found to have a positive and significant effect on the issuance of sukuk. Political stability is found to have a negative effect on the development of sukuk, but not significant. Changes in the growth have a negative and significant influence on the issuance of sukuk.Implication - The results provide a recommendation that in addition to maintaining the current Central Government Financial Statement opinion acquisition at the highest level (unqualified), the government needs to maintain the credibility and accountability of State Budget performance which is manifested through macroeconomic variables and other variables that influence the development of government Sharia securities.Originality - This study provides a new perspective on the influence of audit opinions and various economic factors on the issuance of sukuk in Indonesia, using a comprehensive data set covering the period from 2008 to 2022 and employing the Ordinary Least Squares (OLS) technique for analysis.